Solitary Prosociality in Later Life: An Experience Sampling Study. (October 2022) - Mann, Ajit Singh; Boeder, Jordan; Tse, Dwight C. K.; Graham, Laura; Nakamura, Jeanne
Loneliness is a risk factor for older adults, one exacerbated by the COVID-19 pandemic. Although time spent alone is associated with both loneliness and greater well-being, the experience of solitude may depend on the type of activity pursued. We examined formal prosocial activity as one facilitator of positive solitary experiences. Older adults ( N = 165, M age = 71.13, SD = 5.70) highly committed to prosocial-program work (e.g., tutoring) filled out surveys at six random times every day for a week. Using multilevel modeling, we investigated whether participating in prosocial-program activity alone was associated with greater well-being compared to other solitary activity. While prosocial-program activity did not buffer against negative affect in solitude, it promoted positive affect and relatedness when alone. To the extent that prosocial-program work can facilitate positive solitary experiences by enhancing feelings of connection, it may protect against threats to well-being posed by loneliness in later life.